Treatments for enhancing the biocompatibility of titanium implants - Štěpanovská, Jana; Matějka, Roman; Rosina, Jozef; Bačáková, Lucie; Kolářová, Hana (Biomedical papers of the Medical Faculty of the University Palacký, Olomouc Czech Republic, 2020)
Titanium surface treatment is a crucial process for achieving sufficient osseointegration of an implant into the bone. If the implant does not heal sufficiently, serious complications may occur, e.g. infection, inflammation, aseptic loosening of the implant, or the stress-shielding effect, as a result of which the implant may need to be reoperated. After a titanium graft has been implanted, several interactions are crucial in order to create a strong bone-implant connection. It is essential that cells adhere to the surface of the implant. Surface roughness has a significant influence on cell adhesion, and also on improving and accelerating osseointegration. Other highly important factors are biocompatibility and resistance to bacterial contamination. Bio-inertness of titanium is ensured by the protective film of titanium oxides that forms spontaneously on its surface. This film prevents the penetration of metal compounds, and it is well-adhesive for calcium and phosphate ions, which are necessary for the formation of the mineralized bone structure. Since the presence of the film alone is not sufficient for the biocompatibility of titanium, a suitable surface finish is required to create a firm bone-implant connection. In this review, we explain and compare the most widely-used methods for modulating the surface roughness of titanium implants in order to enhance cell adhesion on the surface of the implant, e.g. plasma spraying, sandblasting, acid etching, laser treatment, sol-gel etc., The methods are divided into three overlapping groups, according to the type of modification.
Keywords: titan; biokompatibilní potahované materiály; Coated Materials, Biocompatible; lidé; osteointegrace; protézy a implantáty; Osseointegration; Titanium; Prostheses and Implants; Humans